Understanding the Reality or Applying the Theory? A Critical Book Review of "Social Backgrounds of the Iran’s Revolution" - Mohammad Ali Hosseini Zadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The Social Backgrounds of Iran’s Revolution, written by Dr. Bashiriyeh and translated by Ali Ardestani, was published by Negahe Moaaser in 1393. The author applied different theories and concepts generally with Marxist orientation to examine the causes, processes, and consequences of Iran’s revolution. The reduction of political struggle to class struggle and linking ideologies to classes and objective interests is the interesting but controversial feature of this book. This paper reviews the book in terms of method, theory, and historical data, and it finally concludes that despite applying various methods and extensive use of data and documentation, detailed explanations of the Islamic Revolution, the emergence of political Islam, and also the nature of the state in the Islamic Republic of Iran have not been offered. This article searches the causes of this failure in the author’s interest and inclination to the Marxist theories and uncritical application of modern concepts and theories in the Iranian society.